131k views
2 votes
2 step equations solve each equation. Show yourselves steps 9+3a=-32x-8=10m/4 - 6 =10-12 + 3p =3-18=6a-6x/-3 + 11 =233+2v=1116=k/3 - 11 -6g -12 = -602a+5-5a+1 combine like terms m-4+3m-2 combine like terms

User Cabezas
by
4.9k points

1 Answer

5 votes

Given the expression;

9 + 3a = -3

Using two step equation;

Step 1: Subtract 9 from both sides

9 + 3a - 9 = -3 - 9

3a = -12

Step 2: Divide both sides by 3

3a = -12

3a/3 = -12/3

a = -4

Hence the value of a is -4

User Ekansh Rastogi
by
5.2k points